Modified fiber type composite high permeable concrete and preparation method thereof

By using composite modified fiber and activated biochar concrete technology, the compressive strength and stability problems of permeable concrete have been solved, achieving a combination of high permeability and high compressive strength, and possessing self-healing and self-cleaning capabilities.

CN117776615BActive Publication Date: 2026-01-06XIANYANG VOCATIONAL TECHN COLLEGE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311659552.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-06
Publication Date
2026-01-06
Estimated Expiration
2043-12-06

AI Technical Summary

Technical Problem

Existing permeable concrete has poor compressive strength and stability, and low permeability, making it difficult to simultaneously meet the requirements of high permeability and high compressive strength.

Method used

Composite modified polypropylene fiber and modified carbon fiber are used, combined with water-based polyurethane emulsion and activated biochar, and composite microbial liquid and photocatalyst are added to form a network structure, which enhances the stability and permeability of concrete, and also has self-healing and self-cleaning capabilities.

Benefits of technology

It improves the compressive strength and permeability of concrete, enhances its stability and crack resistance, and has self-healing and self-cleaning capabilities, which aligns with the concept of sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention discloses a modified fiber-reinforced composite high-permeability concrete and its preparation method in the field of concrete technology. The concrete comprises the following components: silicate cement, fly ash, coarse aggregate, composite fiber, waterborne polyurethane emulsion, activated biochar, water-reducing agent, composite bacterial solution, photocatalyst, and water. By adding modified polypropylene fiber, modified carbon fiber, waterborne polyurethane emulsion, and activated biochar to the concrete raw materials, this invention enhances the mechanical properties of the concrete, improving its stability, compressive strength, and crack resistance. It also increases the void structure of the concrete, further improving its permeability. Simultaneously, the addition of microbial solution and photocatalyst enhances the self-healing and self-cleaning capabilities of the concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of concrete technology, specifically referring to a modified fiber composite high permeability concrete and its preparation method. Background Technology

[0002] People are increasingly valuing green, ecological, and harmonious development, placing greater emphasis not only on the strength and durability of concrete but also on its ecological functions. This has led to a shift from ordinary concrete towards high-porosity, permeable ecological concrete. Permeable concrete is one such ecological concrete, widely used in urban roads and riverbank slopes due to its high porosity and relatively high strength. Permeable concrete not only possesses the functions of traditional concrete but also protects the environment, maintains ecological balance, and offers significant social and ecological benefits.

[0003] Ecological permeable concrete is a porous concrete material whose skeleton is composed of single-graded coarse aggregate. Cement paste coats and binds the coarse aggregate together, creating a large number of interconnected pores. The strength and permeability of permeable concrete are mutually restrictive. Larger aggregate particle sizes result in greater porosity and better permeability, but lower compressive strength; smaller aggregate particle sizes decrease porosity and permeability, but increase compressive strength.

[0004] Therefore, given the above issues, the market needs a type of concrete that is stable, strong in compressive and crack resistance, and highly permeable. Summary of the Invention

[0005] To address the above issues and overcome the shortcomings of existing technologies, this invention provides a modified fiber composite high-permeability concrete and its preparation method. To solve the problems of poor compressive strength, stability, and low permeability of permeable concrete, this invention proposes to increase the stability and void structure of concrete by combining modified polypropylene fibers and modified carbon fibers with water-based polyurethane emulsion and activated biochar, along with fly ash and coarse aggregate. This achieves the technical effect of improving the compressive strength and permeability of concrete. Simultaneously, by adding composite microbial inoculum and photocatalysts, the self-healing and self-cleaning capabilities of the concrete are enhanced.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: The present invention proposes a modified fiber composite high permeability concrete, wherein the concrete comprises the following components in parts by weight: 100-200 parts of silicate cement, 60-80 parts of fly ash, 600-800 parts of coarse aggregate, 50-70 parts of composite fiber, 30-50 parts of waterborne polyurethane emulsion, 20-30 parts of activated biochar, 5-10 parts of water-reducing agent, 5-8 parts of composite bacterial solution, 1-3 parts of photocatalyst, and 80-100 parts of water.

[0007] Preferably, the composite fiber comprises modified polypropylene fiber and modified carbon fiber in a mass ratio of 1:1.5-2;

[0008] Preferably, the modified polypropylene fiber is composed of the following components in parts by weight: 20-30 parts polypropylene fiber, 1 part N-vinylpyrrolidone, 1-2 parts maleic anhydride, and 0.01-0.05 parts azobisisobutyronitrile.

[0009] Preferably, the preparation method of the modified polypropylene fiber specifically includes the following steps:

[0010] N-vinylpyrrolidone and maleic anhydride were dissolved in an alcohol solvent, and azobisisobutyronitrile was added. The mixture was ultrasonically mixed at 200-300W and heated to 70-80℃ under nitrogen protection for 24 hours to obtain a mixed solution. Polypropylene fibers were added to the mixed solution and reacted under ultraviolet light at 100-400W and 365nm. The mixture was filtered, and the residue was washed with deionized water to obtain pre-grafted propylene fibers. The pre-grafted propylene fibers were immersed in 100mL of N,N-dimethylformamide at 50-60℃ for 10-12 hours. After cooling to room temperature, the mixture was filtered, and the precipitate was washed with 70-80% acetone and dried in a constant temperature oven at 50℃ for 1-2 hours to obtain modified polypropylene fibers.

[0011] Preferably, the maleic anhydride has a mass concentration of 10-20 g / L in the alcohol solvent;

[0012] Preferably, the alcohol solvent includes at least one selected from methanol, ethanol, propanol, butanediol, and acetone;

[0013] Preferably, the modified carbon fiber is composed of the following components in parts by weight: 30-60 parts carbon fiber, 1-2 parts tris(hydroxymethyl)aminomethane, 0.5-0.8 parts silane coupling agent, and 1-2 parts dopamine;

[0014] Preferably, the method for preparing the modified carbon fiber specifically includes the following steps:

[0015] Carbon fibers were placed in a muffle furnace and purged under an argon atmosphere with a purge rate of 0.1-0.2 L / min, while maintaining a heating rate of 15-20 °C / min. The temperature was heated to 500-600 °C and calcined for 1-2 hours. After cooling to room temperature, the fibers were washed with deionized water and dried in a 100 °C constant temperature drying oven for 2-3 hours. The fibers were then added to a tris(hydroxymethyl)aminomethane solution and stirred until homogeneous. A silane coupling agent was added, and the fibers were ultrasonically dispersed at 200-300 W for 1-2 hours. Dopamine was added, and the fibers were shaken in a shaker at 150-180 r / min for 1-2 days. The mixture was filtered, and the precipitate was washed with distilled water and dried to obtain modified carbon fibers.

[0016] Preferably, the tris(hydroxymethyl)aminomethane solution has a mass fraction of 3-5% and a pH of 8.0-8.5;

[0017] Preferably, the silane coupling agent comprises at least one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, γ-methacryloyloxypropyltrimethoxysilane, and γ-glycidyl ether propyltrimethoxysilane.

[0018] Preferably, the solid content of the waterborne polyurethane emulsion is 50-60%;

[0019] Preferably, the preparation method of the composite microbial inoculum solution specifically includes the following steps:

[0020] Nitrifying bacteria and denitrifying bacteria are mixed at a mass ratio of 1:1. The mixed bacteria are inoculated into the fermentation medium at a volume of 3-8%. The mixture is fermented on a shaker at 150-180 r / min for 1-2 days at a fermentation temperature of 26-32℃ and a pH of 6.8-7.2 to obtain the compound bacterial agent fermentation broth.

[0021] Preferably, the viable counts of both nitrifying and denitrifying bacteria are above 1 billion / mL;

[0022] Preferably, the fermentation medium comprises: 10-20 parts peptone, 30-50 parts agar, 10-30 parts yeast extract, and 100-200 parts distilled water;

[0023] Preferably, the method for preparing the activated biochar specifically includes the following steps:

[0024] The dehydrated sludge was dried in a 100℃ constant temperature drying oven for 24-36 hours, pulverized, and passed through a 50-mesh sieve to obtain biochar powder. The powder was placed in a muffle furnace and purged under an argon atmosphere with a gas flow rate of 0.1-0.2 L / min, while maintaining a heating rate of 10-20℃ / min. The temperature was heated to 400-700℃ and calcined for 1-2 hours. After cooling to room temperature, the sludge was soaked in 100 mL of 30-35% acetic acid solution for 4-6 hours, then washed with deionized water until the pH reached 6.0-7.0. The sludge was then dried in an 80℃ constant temperature drying oven for 1-2 hours to obtain activated biochar.

[0025] Preferably, the coarse aggregate comprises basalt crushed stone, crushed sand, and slag in a mass ratio of 1:1-1.5:0.5-1; the particle size of the coarse aggregate is 3.0-3.5 mm.

[0026] Preferably, the water-reducing agent includes at least one of polycarboxylate-based water-reducing agents, naphthalene-based water-reducing agents, aminosulfonate-based water-reducing agents, and lignin sulfonate-based water-reducing agents;

[0027] The polycarboxylate superplasticizer is selected from DH-4004 type polycarboxylate high-performance superplasticizer and Point-TBS type polycarboxylate high-performance superplasticizer;

[0028] The naphthalene-based water-reducing agent is selected from sodium tri(1-methylethyl)naphthalenesulfonate and sodium dibutylnaphthalenesulfonate;

[0029] The aminosulfonate-based water-reducing agent is selected from TL-type aminosulfonate-based high-efficiency water-reducing agent and AS-type aminosulfonate-based high-efficiency water-reducing agent;

[0030] The lignin sulfonate-based water-reducing agent is selected from sodium lignin sulfonate and calcium lignin sulfonate;

[0031] Preferably, the photocatalyst is composed of titanium dioxide and zinc oxide in a mass ratio of 2:1-1.5.

[0032] This invention also provides a method for preparing modified fiber-reinforced composite high-permeability concrete, specifically including the following steps:

[0033] S1. Mix silicate cement, fly ash, and coarse aggregate evenly to obtain a mixture.

[0034] S2. Add composite fiber, waterborne polyurethane emulsion, activated biochar, water-reducing agent, composite bacterial solution, photocatalyst and water to the mixture obtained in step S1, and mix evenly in a concrete mixer to obtain modified fiber composite high permeability concrete.

[0035] The beneficial effects achieved by this invention are as follows:

[0036] This invention provides a modified fiber composite high permeability concrete. By adding composite fibers, water-based polyurethane emulsion, and activated biochar to the concrete substrate, the stability, compressive strength, and crack resistance of the concrete can be improved, and the permeability can be increased. By adding composite microbial liquid and photocatalyst, the self-healing and self-cleaning ability of the concrete can be improved.

[0037] The composite fiber of this invention is composed of modified polypropylene fiber and modified carbon fiber. The modified polypropylene fiber is obtained by modifying N-vinylpyrrolidone and maleic anhydride. N-vinylpyrrolidone is amphiphilic and is a monomer with a stable five-membered ring structure. Adding N-vinylpyrrolidone to the surface of the polypropylene fiber enhances its rigid structure. Grafting maleic anhydride onto the polypropylene fiber introduces a large number of hydrophilic groups, improving the hygroscopicity of the polypropylene fiber. The N-vinylpyrrolidone-maleic anhydride copolymer has good compatibility and can enhance the interaction between the modified polypropylene fiber and other substances. The modified carbon fiber improves the adhesion of concrete, thereby enhancing its stability. Modified carbon fiber is obtained by modifying carbon fibers with silane coupling agents and dopamine. The silane coupling agent forms a hydrophilic siloxane layer on the carbon fiber surface, while the hydroxyl and amino groups of dopamine molecules have strong hydrogen bond interactions with the carbon fiber, which helps improve the surface activity and adhesion of the carbon fiber. The modified carbon fiber helps improve its dispersibility in concrete. The modified polypropylene fiber and modified carbon fiber work together in concrete, forming a network structure through covalent and ionic bonds, strengthening the mechanical properties of concrete and increasing its compressive strength. The invention offers several advantages: Firstly, polyurethane possesses a unique porous structure, resulting in high permeability of the water-based polyurethane emulsion. High-temperature calcination of waste sludge creates a loose, porous structure. Soaking in acetic acid solution helps remove impurities and oxides from the surface of the biochar, while simultaneously expanding the pore structure and increasing its specific surface area. The addition of water-based polyurethane emulsion and activated biochar provides channels for water molecule impregnation, thereby improving the permeability of the concrete material. Secondly, when cracks appear in the concrete, the water-based polyurethane emulsion can fill these tiny cracks. Nitrifying and denitrifying bacteria, in the presence of water and oxygen, promote carbonate precipitation, repairing cracks and improving the concrete's crack resistance and self-healing ability. This helps extend the lifespan of concrete structures and reduce maintenance costs. Thirdly, photocatalysts, added to the concrete in nanoparticle form, generate photoelectrons and holes under sunlight, promoting photocatalytic reactions and helping to degrade air pollutants, reducing pollution on building surfaces and achieving a self-cleaning effect. Finally, this invention fully utilizes waste sludge, turning it into a valuable resource, increasing the added value of waste materials, protecting the ecological environment, and aligning with the concept of sustainable development. Attached Figure Description

[0038] Figure 1 This is an electron microscopy scan of the microstructure of the composite fiber obtained in Example 1 of the present invention.

[0039] Figure 2 This is a 500x magnified electron microscope scan of the surface of the activated biochar prepared in Example 1 of the present invention;

[0040] Figure 3The graphs show the results of the compressive strength of the concrete described in Examples 1-3 and Comparative Examples 1-4 of this invention.

[0041] Figure 4 The graphs show the results of the permeability of concrete described in Examples 1-3 and Comparative Examples 1, 2, 5, and 6 of this invention.

[0042] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used together with the embodiments of the invention to explain the invention and do not constitute a limitation thereof. Detailed Implementation

[0043] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0044] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those familiar to those skilled in the art. Furthermore, any methods and materials similar to or equivalent to those described herein may be applied to this invention. The preferred embodiments and materials described herein are for illustrative purposes only and do not limit the scope of this application.

[0045] Unless otherwise specified, the experimental methods used in the following examples are conventional methods; unless otherwise specified, the test materials and test strains used in the following examples were purchased from commercial channels; and all quantities are parts by weight.

[0046] The strains involved in this invention originate from the following sources:

[0047] Nitrifying bacteria: Gordonia hydrophobica, strain number CICC 24205, was selected and purchased from the China Industrial Microbial Culture Collection Center.

[0048] Denitrifying bacteria: Pseudomonas aeruginosa, strain number CICC 23618, was selected and purchased from the China Industrial Microbial Culture Collection Center.

[0049] Example 1

[0050] A modified fiber-reinforced composite permeable concrete, wherein the concrete is composed of the following components in parts by weight: 100 parts silicate cement, 60 parts fly ash, 240 parts basalt crushed stone, 240 parts crushed sand, 120 parts slag, 20 parts modified polypropylene fiber, 30 parts modified carbon fiber, 30 parts waterborne polyurethane emulsion with a solid content of 50%, 20 parts activated biochar, 5 parts polycarboxylate superplasticizer, 5 parts composite microbial inoculum, 0.6 parts titanium dioxide, 0.4 parts zinc oxide, and 80 parts water;

[0051] The preparation method of modified polypropylene fibers specifically includes the following steps:

[0052] 1g of N-vinylpyrrolidone and 1g of maleic anhydride were dissolved in 100mL of methanol, and 0.01g of azobisisobutyronitrile was added. The mixture was ultrasonically mixed at 200°C and heated to 70°C under nitrogen protection for 24 hours to obtain a mixed solution. 20g of polypropylene fiber was added to the mixed solution and reacted under ultraviolet light at 100W and 365nm. The mixture was filtered, and the residue was washed with deionized water to obtain pre-grafted propylene fiber. The pre-grafted propylene fiber was immersed in 100mL of N,N-dimethylformamide at 50°C for 10 hours. After cooling to room temperature, the mixture was filtered, and the precipitate was washed with 70% acetone and dried in a constant temperature oven at 50°C for 1 hour to obtain modified polypropylene fiber.

[0053] The preparation method of modified carbon fiber specifically includes the following steps:

[0054] 1 g of tris(hydroxymethyl)aminomethane was dissolved in 100 mL of water to obtain a tris(hydroxymethyl)aminomethane solution. The solution was washed with 3% hydrochloric acid until the pH reached 8.0, resulting in a weakly alkaline buffer solution. 30 g of carbon fiber was placed in a muffle furnace and purged under an argon atmosphere with a purge rate of 0.1 L / min. The temperature was maintained at 15 °C / min and heated to 500 °C for 1 h. After cooling to room temperature, the carbon fiber was washed with deionized water and dried in a 100 °C oven for 2 h. The carbon fiber was then added to the weakly alkaline buffer solution, and 0.5 g of γ-aminopropyltrimethoxysilane was added. The mixture was ultrasonically dispersed at 200 W for 1 h to obtain a dispersion. 1 g of dopamine was added to the dispersion, and the mixture was shaken on a shaker at 150 r / min for 1 day. The mixture was filtered, and the precipitate was washed with distilled water and dried to obtain modified carbon fiber.

[0055] The preparation method of the compound microbial inoculum solution specifically includes the following steps:

[0056] Nitrifying bacteria and denitrifying bacteria were mixed at a mass ratio of 1:1. The mixed bacteria were inoculated into the fermentation medium at 3% of the fermentation medium volume. The mixture was fermented on a shaker at 150 r / min for 1 day at a fermentation temperature of 26℃ and a pH of 6.8 to obtain the compound bacterial agent fermentation broth.

[0057] The viable counts of both nitrifying and denitrifying bacteria were ≥1 billion CFU / mL;

[0058] The fermentation medium consists of: 10 parts peptone, 30 parts agar, 10 parts yeast extract, and 100 parts distilled water;

[0059] The preparation method of activated biochar specifically includes the following steps:

[0060] 20g of dehydrated sludge was dried in a 100℃ constant temperature drying oven for 24h, pulverized, and passed through a 50-mesh sieve to obtain biochar powder. The powder was placed in a muffle furnace and purged under an argon atmosphere with a gas flow rate of 0.1L / min, while maintaining a heating rate of 10℃ / min. The temperature was heated to 400℃ and calcined for 1h. After cooling to room temperature, the sludge was soaked in 100mL of 30% acetic acid solution for 4h, then washed with deionized water until the pH reached 6.0. The sludge was then dried in an 80℃ constant temperature drying oven for 1h to obtain activated biochar.

[0061] This invention also provides a method for preparing modified fiber-reinforced composite high-permeability concrete, specifically including the following steps:

[0062] S1. Mix silicate cement, fly ash, and coarse aggregate evenly to obtain a mixture.

[0063] S2. Add composite fiber, waterborne polyurethane emulsion, activated biochar, water-reducing agent, composite bacterial solution, photocatalyst and water to the mixture obtained in step S1, and mix evenly in a concrete mixer to obtain modified fiber composite high permeability concrete.

[0064] Example 2

[0065] A modified fiber composite permeable concrete, the concrete being composed of the following components in parts by weight: 150 parts silicate cement, 70 parts fly ash, 233 parts basalt crushed stone, 280 parts crushed sand, 187 parts slag, 22 parts modified polypropylene fiber, 38 parts modified carbon fiber, 40 parts waterborne polyurethane emulsion with a solid content of 55%, 25 parts activated biochar, 7.5 parts naphthalene-based water-reducing agent, 6.5 parts composite microbial inoculum, 1.6 parts titanium dioxide, 0.4 parts zinc oxide, and 90 parts water;

[0066] The preparation method of modified polypropylene fibers specifically includes the following steps:

[0067] 1g of N-vinylpyrrolidone and 1.5g of maleic anhydride were dissolved in 100mL of methanol, and 0.03g of azobisisobutyronitrile was added. The mixture was ultrasonically mixed at 250W and heated to 75℃ under nitrogen protection for 24h to obtain a mixed solution. 20g of polypropylene fiber was added to the mixed solution and reacted under UV conditions of 250W and 365nm. After filtration, the residue was washed with deionized water to obtain pre-grafted propylene fiber. The pre-grafted propylene fiber was immersed in 100mL of N,N-dimethylformamide at 55℃ for 11h. After cooling to room temperature, the mixture was filtered, and the precipitate was washed with 75% acetone and dried in a constant temperature oven at 50℃ for 1.5h to obtain modified polypropylene fiber.

[0068] The preparation method of modified carbon fiber specifically includes the following steps:

[0069] 1.5 g of tris(hydroxymethyl)aminomethane was dissolved in 100 mL of water to obtain a tris(hydroxymethyl)aminomethane solution. The solution was washed with 4% hydrochloric acid until the pH reached 8.2, resulting in a weakly alkaline buffer solution. 45 g of carbon fiber was placed in a muffle furnace and purged under an argon atmosphere with a purge rate of 0.15 L / min. The temperature was maintained at 18 °C / min and heated to 550 °C for 1.5 h. After cooling to room temperature, the carbon fiber was washed with deionized water and dried in a 100 °C oven for 2.5 h. The carbon fiber was then added to the weakly alkaline buffer solution, and 0.65 g of γ-aminopropyltriethoxysilane was added. The mixture was ultrasonically dispersed at 250 W for 1.5 h to obtain a dispersion. 1.5 g of dopamine was added to the dispersion, and the mixture was shaken on a shaker at 165 r / min for 1.5 days. The mixture was filtered, and the precipitate was washed with distilled water and dried to obtain modified carbon fiber.

[0070] The preparation method of the compound microbial inoculum solution specifically includes the following steps:

[0071] Nitrifying bacteria and denitrifying bacteria were mixed at a mass ratio of 1:1. The mixed bacteria were inoculated into the fermentation medium at 5% of the fermentation medium volume. The mixture was fermented on a shaker at 165 r / min for 1.5 days at a fermentation temperature of 29℃ and a pH of 7.0 to obtain the compound bacterial agent fermentation broth.

[0072] The viable counts of both nitrifying and denitrifying bacteria were ≥1 billion CFU / mL;

[0073] The fermentation medium consists of: 15 parts peptone, 40 parts agar, 20 parts yeast extract, and 150 parts distilled water.

[0074] The preparation method of activated biochar specifically includes the following steps:

[0075] 25g of dehydrated sludge was dried in a 100℃ constant temperature drying oven for 30h, pulverized, and passed through a 50-mesh sieve to obtain biochar powder. The powder was placed in a muffle furnace and purged under an argon atmosphere with a gas flow rate of 0.15L / min, while maintaining a heating rate of 15℃ / min. The powder was heated to 550℃ and calcined for 1.5h. After cooling to room temperature, the powder was soaked in 100mL of 32.5% acetic acid solution for 5h, then washed with deionized water until the pH reached 6.5. The powder was then dried in an 80℃ constant temperature drying oven for 1.5h to obtain activated biochar.

[0076] The present invention also provides a method for preparing modified fiber composite high permeability concrete, wherein the preparation method is carried out in accordance with Example 1.

[0077] Example 3

[0078] A modified fiber composite high permeable concrete, the concrete being composed of the following components in parts by weight: 200 parts silicate cement, 80 parts fly ash, 229 parts basalt crushed stone, 342 parts crushed sand, 229 parts slag, 23 parts modified polypropylene fiber, 47 parts modified carbon fiber, 50 parts waterborne polyurethane emulsion with a solid content of 60%, 30 parts activated biochar, 10 parts aminosulfonate-based water-reducing agent, 8 parts composite microbial inoculum, 1.7 parts titanium dioxide, 1.3 parts zinc oxide, and 100 parts water.

[0079] The preparation method of modified polypropylene fibers specifically includes the following steps:

[0080] 1g of N-vinylpyrrolidone and 2g of maleic anhydride were dissolved in 100mL of methanol, and 0.05g of azobisisobutyronitrile was added. The mixture was ultrasonically mixed at 300W and heated to 80℃ under nitrogen protection for 24h to obtain a mixed solution. 20g of polypropylene fiber was added to the mixed solution and reacted under UV conditions of 400W and 365nm. After filtration, the residue was washed with deionized water to obtain pre-grafted propylene fiber. The pre-grafted propylene fiber was immersed in 100mL of N,N-dimethylformamide at 60℃ for 12h. After cooling to room temperature, the mixture was filtered, and the precipitate was washed with 80% acetone and dried in a constant temperature oven at 50℃ for 2h to obtain modified polypropylene fiber.

[0081] The preparation method of modified carbon fiber specifically includes the following steps:

[0082] 2g of tris(hydroxymethyl)aminomethane was dissolved in 100mL of water to obtain a tris(hydroxymethyl)aminomethane solution. The solution was washed with 5% hydrochloric acid until the pH reached 8.5, resulting in a weakly alkaline buffer solution. 60g of carbon fiber was placed in a muffle furnace and purged under an argon atmosphere with a purge rate of 0.2L / min. The temperature was maintained at 20℃ / min and heated to 600℃ for 2 hours. After cooling to room temperature, the carbon fiber was washed with deionized water and dried in a 100℃ constant temperature drying oven for 3 hours. The carbon fiber was then added to the weakly alkaline buffer solution, and 0.8g of γ-mercaptopropyltrimethoxysilane was added. The mixture was ultrasonically dispersed at 300W for 2 hours to obtain a dispersion. 2g of dopamine was added to the dispersion, and the mixture was shaken on a shaker at 180r / min for 2 days. The mixture was filtered, and the precipitate was washed with distilled water and dried to obtain modified carbon fiber.

[0083] The preparation method of the compound microbial inoculum solution specifically includes the following steps:

[0084] Nitrifying bacteria and denitrifying bacteria were mixed at a mass ratio of 1:1. The mixed bacteria were inoculated into the fermentation medium at 8% of the fermentation medium volume. The mixture was fermented on a shaker at 180 r / min for 2 days at a fermentation temperature of 32℃ and a pH of 7.2 to obtain the compound bacterial agent fermentation broth.

[0085] The viable counts of both nitrifying and denitrifying bacteria were ≥1 billion CFU / mL;

[0086] The fermentation medium consists of: 15 parts peptone, 40 parts agar, 20 parts yeast extract, and 150 parts distilled water.

[0087] The preparation method of activated biochar specifically includes the following steps:

[0088] 30g of dehydrated sludge was dried in a 100℃ constant temperature drying oven for 36h, pulverized, and passed through a 50-mesh sieve to obtain biochar powder. The powder was placed in a muffle furnace and purged under an argon atmosphere with a gas flow rate of 0.2L / min, while maintaining a heating rate of 20℃ / min. The temperature was heated to 700℃ and calcined for 2h. After cooling to room temperature, the sludge was soaked in 100mL of 35% acetic acid solution for 6h, then washed with deionized water until the pH reached 7.0. The sludge was then dried in an 80℃ constant temperature drying oven for 2h to obtain activated biochar.

[0089] In addition, the present invention also provides a method for preparing modified fiber composite high permeability concrete, wherein the preparation method is carried out in accordance with Example 1.

[0090] Comparative Example 1

[0091] This comparative example provides a modified fiber composite high permeability concrete, which differs from Example 1 only in that the polypropylene fiber is not modified, while the other components, component content, and preparation method are the same as in Example 1.

[0092] Comparative Example 2

[0093] This comparative example provides a modified fiber composite permeable concrete, which differs from Example 1 only in that the carbon fiber is not modified, while the other components, component content, and preparation method are the same as in Example 1.

[0094] Comparative Example 3

[0095] This comparative example provides a modified fiber composite high permeability concrete, which differs from Example 1 only in that the concrete does not contain any polypropylene fibers, while the other components, component contents, and preparation methods are the same as in Example 1.

[0096] Comparative Example 4

[0097] This comparative example provides a modified fiber composite high permeability concrete, which differs from Example 1 only in that the concrete does not contain any carbon fiber, while the other components, component content, and preparation method are the same as in Example 1.

[0098] Comparative Example 5

[0099] This comparative example provides a modified fiber composite high permeability concrete, which differs from Example 1 only in that the concrete does not contain water-based polyurethane emulsion, while the other components, component contents, and preparation methods are the same as in Example 1.

[0100] Comparative Example 6

[0101] This comparative example provides a modified fiber composite high permeability concrete, which differs from Example 1 only in that no biochar is added to the concrete, while the other components, component content, and preparation method are the same as in Example 1.

[0102] Comparative Example 7

[0103] This comparative example provides a modified fiber composite high permeability concrete, which differs from Example 1 only in that the concrete does not contain added microbial agents, while the other components, component contents, and preparation methods are the same as in Example 1.

[0104] Comparative Example 8

[0105] This comparative example provides a modified fiber composite high permeability concrete, which differs from Example 1 only in that the concrete does not contain a photocatalyst, while the other components, component contents, and preparation methods are the same as in Example 1.

[0106] Experimental Example 1

[0107] In this experimental example, the composite fiber described in Example 1 was scanned using an electron microscope. Figure 1 This is an electron microscopy scan of the microstructure of the composite fiber obtained in Example 1 of the present invention.

[0108] Experiment Example 2

[0109] In this experimental example, the surface of the activated biochar described in Example 1 was scanned using an electron microscope. Figure 2 This is a 500x magnified electron microscope scan of the surface of the activated biochar prepared in Example 1 of the present invention.

[0110] Experimental Example 3

[0111] This experimental example demonstrates the compressive strength determination of the concrete described in Examples 1-3 and Comparative Examples 1-4. The specific method is as follows: Referring to the national standard GB / T50081-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete", the compressive strength of the specimens was tested using a JES-2000A compression testing machine after 28 days. The accuracy of the compression testing machine was not less than 2%. The specimens used were standard cubes of 150mm × 150mm × 150mm. During the test, a continuous and uniform loading method was adopted, with a loading rate of 0.3-0.5 MPa / s as required by the design. The compressive strength of the concrete cube was calculated according to the following formula:

[0112] ;

[0113] Among them, f cc F represents the compressive strength of the concrete cube (MPa); F represents the failure load of the specimen (N); A represents the bearing area of ​​the specimen (mm²). 2 ).

[0114] Figure 3 The figures show the compressive strength results of the concrete described in Examples 1-3 and Comparative Examples 1-4 of this invention. As shown, after 28 days, the compressive strength of Examples 1-3 reached 62.7-65.2 MPa. This was achieved by modifying polypropylene fibers with N-vinylpyrrolidone and maleic anhydride, and carbon fibers modified with silane coupling agents and dopamine. Through covalent and ionic bonds, these materials enhanced the mechanical properties of the concrete, improving its strength and stability. Comparative Example 1 had a compressive strength of 45.6 MPa, and Comparative Example 2 had a compressive strength of 43.1 MPa. The unmodified polypropylene fibers... Unmodified carbon fibers are unevenly dispersed in concrete and cannot effectively interact with the cement paste, leading to unstable concrete performance and decreased compressive strength. The compressive strength of Comparative Example 3 is only 38.9 MPa, and that of Comparative Example 4 is only 31.2 MPa. Polypropylene fibers are mainly used to control the crack width of concrete and improve its toughness and impact resistance, thus affecting its compressive strength. Carbon fibers are mainly used to improve the strength and durability of concrete. Only when the two work together can they achieve their maximum effect to improve the compressive strength of concrete.

[0115] Experiment Example 4

[0116] This experiment measured the permeability coefficient of the concrete described in Examples 1-3 and Comparative Examples 1, 2, 5, and 6. The specific method was as follows: Seven cubic concrete specimens, each 100mm × 100mm × 100mm, were prepared according to the concrete composition and preparation methods described in Examples 1-3 and Comparative Examples 1, 2, 5, and 6. A rectangular transparent device was prepared, open at both the top and bottom, with a fixed scale of 0-150mm on one side. The surface of the concrete specimen was sealed with putty and placed inside the device. The gap between the concrete specimen and the device was sealed with putty. Water was poured into the device to above the 150mm mark. A stopwatch was started when the water level was exactly 150mm. The time was recorded as t when the water level dropped to 0mm. The permeability coefficient when the water level dropped from 150mm to zero was calculated using the following formula:

[0117] ;

[0118] Where K is the permeability coefficient (mm / s) and t is the time (s) it takes for the water level to drop from 150mm to zero.

[0119] Experimental Example 5

[0120] This experimental example measures the porosity of the concrete described in Examples 1-3 and Comparative Examples 1, 2, 5, and 6. The specific method is as follows: Seven cubic concrete specimens, each 100mm × 100mm × 100mm in size, were prepared according to the concrete composition and preparation method described in Examples 1-3 and Comparative Examples 1, 2, 5, and 6. After curing in a standard curing room at 20℃ for 7 days, the concrete specimens were dried in a 100℃ constant temperature drying oven for 24 hours, and the volume V was measured. The concrete specimens were then immersed in water for 12 hours, and the mass m1 was measured. Finally, the concrete specimens were dried in a 100℃ constant temperature drying oven for 12 hours, and the mass m2 was measured. The porosity of the concrete was calculated using the following formula:

[0121] ;

[0122] Where P is porosity (%) and V is volume (mm³). 3 m1 is the wet mass (g), and m2 is the dry mass (g).

[0123] Figure 4The figures show the permeability results of the concrete described in Examples 1-3 and Comparative Examples 1, 2, 5, and 6 of this invention. The concrete in Examples 1-3 has a permeability coefficient of 2.59-2.71 mm / s and a porosity of 21.2-22.3%. By adding modified polypropylene fiber, modified carbon fiber, waterborne polyurethane emulsion, and activated biochar, the mechanical properties of the concrete are enhanced, while simultaneously attracting water molecules and providing channels for their flow, thereby improving its permeability. The concrete in Comparative Examples 1 and 2 has permeability coefficients of 2.34 mm / s and 2.38 mm / s, respectively, and porosities of 18.2% and 17.9%, respectively. The concrete polypropylene fibers in Example 1 were unmodified, and the carbon fibers in Comparative Example 2 were unmodified. The unmodified composite fibers have a dense internal structure, lack a porous structure, and lack hydrophilic groups that can attract water molecules, which reduces the permeability of the concrete. The permeability coefficients of the concrete in Comparative Examples 5 and 6 were 1.65 mm / s and 1.52 mm / s, respectively, and the porosities were 13.2% and 12.1%, respectively. The concrete in Comparative Examples 5 and 6 did not contain water-based polyurethane emulsion or activated biochar, and the concrete lacked a pore structure. When exposed to water, it could not provide a channel for water molecules to flow, which greatly reduced the porosity of the concrete and affected its permeability.

[0124] Experimental Example 6

[0125] The mechanical properties and permeability of the concrete described in Examples 1-3 and Comparative Examples 1-8 were tested. The test results are shown in Table 1. The test methods are as follows:

[0126] 1. Flexural strength: The flexural strength of concrete was tested according to the methods specified in GB / T50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete";

[0127] 2. Freeze-thaw resistance: The mass loss rate and relative dynamic modulus of elasticity of concrete were tested according to the methods specified in GB / T50082-2019 "Standard for Test Methods of Freeze-Thaw Resistance of Concrete".

[0128] 3. Crack resistance: The crack resistance rate of concrete shall be tested according to the methods specified in GB / T50082 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete";

[0129] Table 1 Results of concrete performance testing

[0130]

[0131] The experimental data from Examples 1-3 and Comparative Examples 1-8 in Table 1 show that polypropylene fibers modified with N-vinylpyrrolidone and maleic anhydride, and carbon fibers modified with silane coupling agents and dopamine, enhance the mechanical properties of concrete through covalent and ionic bonds, improving its strength, stability, and crack resistance. Polypropylene fibers alone primarily improve the compressive strength, flexural strength, and durability of concrete, while carbon fibers alone primarily improve its crack resistance and toughness. Only through their synergistic effect can multiple mechanical properties of concrete be enhanced. Waterborne polyurethane emulsions improve both the permeability and crack resistance of concrete. Mixing activated biochar with coarse aggregate increases the pore structure of concrete, effectively improving its permeability. Microbial agents help repair cracks in concrete and enhance its self-healing ability. Photocatalysts help degrade air pollutants, reduce surface contamination, achieve self-cleaning effects, and thus extend the service life of concrete.

[0132] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

[0133] The present invention and its embodiments have been described above. This description is not restrictive, and the accompanying drawings are only one embodiment of the present invention. The actual application is not limited to this. In conclusion, if those skilled in the art are inspired by this description and design similar methods and embodiments without departing from the spirit of the present invention, they should all fall within the protection scope of the present invention.

Claims

1. A modified fiber composite high permeable concrete, characterized by: The concrete is composed of the following components by weight: Portland cement 100-200 parts, fly ash 60-80 parts, coarse aggregate 600-800 parts, composite fiber 50-70 parts, water-based polyurethane emulsion 30-50 parts, activated biochar 20-30 parts, water reducing agent 5-10 parts, composite microbial bacteria liquid 5-8 parts, photocatalyst 1-3 parts, and water 80-100 parts; The composite fiber includes modified polypropylene fiber and modified carbon fiber in a mass ratio of 1:1.5-2; The modified polypropylene fiber is composed of the following components by weight: polypropylene fiber 20-30 parts, N-vinyl pyrrolidone 1 part, maleic anhydride 1-2 parts, and azobisisobutyronitrile 0.01-0.05 parts; The modified carbon fiber is composed of the following components by weight: carbon fiber 30-60 parts, tris(hydroxymethyl) aminomethane 1-2 parts, silane coupling agent 0.5-0.8 parts, and dopamine 1-2 parts; The preparation method of the modified polypropylene fiber specifically includes the following steps: N-vinyl pyrrolidone and maleic anhydride are dissolved in an alcohol solvent, azobisisobutyronitrile is added, ultrasonic mixing is performed under the condition of 200-300 W, heating is performed to 70-80℃ under nitrogen protection, and reaction is performed for 24 h to obtain a mixed solution; polypropylene fiber is added to the mixed solution, reaction occurs under the condition of ultraviolet at 100-400 W and 365 nm, filtration is performed, the residue is washed with deionized water, and pre-grafted propylene fiber is obtained; the pre-grafted propylene fiber is soaked in 100 mL N,N-dimethylformamide at 50-60℃ for 10-12 h, cooled to room temperature, filtered, the precipitate is washed with 70-80% (mass fraction) acetone, and dried in a 50℃ constant temperature oven for 1-2 h to obtain modified polypropylene fiber; The mass concentration of the maleic anhydride in the alcohol solvent is 10-20 g / L; The alcohol solvent includes at least one of methanol, ethanol, propanol, butanediol, and acetone; The preparation method of the modified carbon fiber specifically includes the following steps: The carbon fiber is placed in a muffle furnace, purged with argon atmosphere at a flow rate of 0.1-0.2 L / min, and heated to a temperature of 500-600℃ at a heating rate of 15-20℃ / min, calcined for 1-2 h, cooled to room temperature, washed with deionized water, and dried in a 100℃ constant temperature drying oven for 2-3 h; after stirring uniformly in a tris(hydroxymethyl) aminomethane solution, a silane coupling agent is added, ultrasonic dispersion is performed for 1-2 h under the condition of 200-300 W, dopamine is added, and shaking is performed in a 150-180 r / min incubator shaker for 1-2 d, filtered, the precipitate is washed and dried with distilled water, and modified carbon fiber is obtained; The mass fraction in the tris(hydroxymethyl) aminomethane solution is 3-5%, and the pH is 8.0-8.5; The silane coupling agent includes at least one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, γ-methacryloyloxypropyltrimethoxysilane, and γ-glycidyl ether propyltrimethoxysilane.

2. The modified fiber composite high pervious concrete according to claim 1, characterized in that: The solid content of the aqueous polyurethane emulsion is 50-60%.

3. The modified fiber composite high pervious concrete according to claim 2, characterized in that: The coarse aggregate comprises basalt gravel, crushed sand and slag in a mass ratio of 1:1-1.5:0.5-1, and the particle size of the coarse aggregate is 3.0-3.5 mm.

4. The modified fiber composite high pervious concrete according to claim 3, characterized in that: The water reducing agent comprises at least one of polycarboxylic acid type water reducing agent, naphthalene type water reducing agent, amino sulfonate type water reducing agent and lignin sulfonate type water reducing agent.

5. The modified fiber composite high pervious concrete according to claim 4, characterized in that: The preparation method of the composite microbial liquid specifically comprises the following steps: The nitrifying bacteria and denitrifying bacteria are mixed in a mass ratio of 1:1, the mixed bacteria are inoculated in a fermentation medium at 3-8% of the volume of the fermentation medium, and the fermentation medium is subjected to 150-180 r / min shaking culture for 1-2 days at a fermentation temperature of 26-32 DEG C and a pH of 6.8-7.2 to obtain a composite microbial agent fermentation liquor. The viable bacterial count of the nitrifying bacteria and denitrifying bacteria is more than 1 billion / mL. The fermentation medium comprises 10-20 parts of proteose peptone, 30-50 parts of agar, 10-30 parts of yeast extract and 100-200 parts of distilled water.

6. The modified fiber composite high pervious concrete according to claim 5, characterized in that: The photocatalyst is composed of titanium dioxide and zinc oxide in a mass ratio of 2:1-1.

5.

7. The modified fiber composite high pervious concrete according to claim 6, characterized in that: The preparation method of the activated biochar specifically comprises the following steps: The dewatered sludge is dried in a constant-temperature drying oven at 100 DEG C for 24-36 hours, crushed, and sieved through a 50-mesh sieve to obtain biochar powder, which is placed in a muffle furnace, purged under an argon atmosphere at an aeration rate of 0.1-0.2 L / min, and heated at a heating rate of 10-20 DEG C / min to a temperature of 400-700 DEG C, and calcined for 1-2 hours, and then cooled to room temperature, soaked in 100 mL of an acetic acid solution with a mass fraction of 30-35% for 4-6 hours, washed with deionized water until the pH is 6.0-7.0, and placed in a constant-temperature drying oven at 80 DEG C for 1-2 hours to obtain activated biochar.

8. A preparation method of the modified fiber composite high-water-permeable concrete according to any one of claims 1-7, characterized in that: S1, uniformly mixing silicate cement, fly ash and coarse aggregate to obtain a mixture; S2, adding composite fiber, aqueous polyurethane emulsion, activated biochar, water reducing agent, composite microbial liquid, photocatalyst and water to the mixture obtained in step S1, and uniformly mixing in a concrete mixer to obtain modified fiber composite high-water-permeable concrete.

Citation Information

Patent Citations

  • Preparation method of metal base carbon fiber composite material

    CN107354406A

  • Fiber-reinforced recycled aggregate pervious concrete

    CN114804763A